Safety of transesophageal echocardiography during transcatheter edge-to-edge tricuspid valve repair: A single-center experience - Hellhammer, Katharina; Schueler, Robert; Eißmann, Mareike; Schumacher, Brigitte; Wolf, Alexander; Bruder, Oliver; Schmitz, Thomas; Lambers, Moritz (Frontiers in Cardiovascular Medicine, 2022)
Objectives We aimed to determine transesophageal echocardiography (TEE) related complications during Transcatheter edge-to-edge tricuspid valve repair (TTVR). Background TEE is essential to guide structural heart disease (SHD) interventions. TTVR has become an evolving procedure for high-risk patients not suitable for surgery. Whether this complex procedure is associated with TEE related complications is not known so far. Methods We retrospectively analyzed 64 consecutive patients undergoing TTVR between 2019 and 2021 with the TriClip system (Abbott, Chicago, IL, USA) at our center. All procedures were performed under general anesthesia (GA). TEE related complications were classified as major and minor complications. Results TEE related complications were observed in two patients (3.1%) with one major complication (1.6%) and one minor complication (1.6%). In one patient perforation of the esophageal mucosa requiring red blood cell transfusion was observed, the other patient had hematemesis due to minor esophageal and gastric lesions without the need for blood transfusion. Both patients recovered during hospital stay with no persistent symptoms at discharge. Conclusions TEE related complications during TTVR are clinically relevant occurring in 3.1% of the patients. Further investigations are needed to identify potential risk factors and patients at high risk to develop a TEE related complication in the course of TTVR.